Insights into idarubicin antimicrobial activity against methicillin-resistant Staphylococcus aureus. Issue 1 (31st December 2020) - She, Pengfei; Li, Shijia; Zhou, Linying; Luo, Zhen; Liao, Jinfeng; Xu, Lanlan; Zeng, Xianghai; Chen, Ti; Liu, Yaqian; Wu, Yong
ABSTRACT: Background: MRSA is a major concern in community settings and in health care. The emergence of biofilms and persister cells substantially increases its antimicrobial resistance. It is very urgent to develop new antimicrobials to solve this problem. Objective: Idarubicin was profiled to assess its antimicrobial effects in vitro and in vivo, and the underlying mechanisms. Methods: We investigated the antimicrobial effects of idarubicin against MRSA by time-kill analysis. The antibiofilm efficacy of idarubicin was assessed by crystal violet and XTT staining, followed by laser confocal microscopy observation. The mechanisms underlying the antimicrobial effects were studied by transmission electron microscopy, all-atom molecular dynamic simulations, SYTOX staining, surface plasma resonance, and DNA gyrase inhibition assay. Further, we addressed the antimicrobial efficacy in wound and subcutaneous abscess infection in vivo . Results: Idarubicin kills MRSA cells by disrupting the lipid bilayers and interrupting the DNA topoisomerase IIA subunits, and idarubicin shows synergistic antimicrobial effects with fosfomycin. Through synergy with a single dose treatment fosfomycin and the addition of the cell protector amifostine, the cytotoxicity and cardiotoxicity of idarubicin were significantly reduced without affecting its antimicrobial effects. Idarubicin alone or in combination with fosfomycin exhibited considerable efficacy in a subcutaneous abscess mouse model of MRSA infection. In addition, idarubicin also showed a low probability of causing resistance and good postantibiotic effects. Conclusions: Idarubicin and its analogs have the potential to become a new class of antimicrobials for the treatment of MRSA-related infections.